Geo Bogza și provincia ca aventură – note despre O sută șaptezeci și cinci de minute la Mizil - Paul Cernat (Revista de Istorie și Teorie Literară)
This study reinterprets an inter-wars text from the prose of Romanian writer Geo Bogza – the experimental reportage One Hundred and Seventy Five Minutes in Mizil [O sută şaptezeci şi cinci de minute la Mizil], from a multiply focused perspective. Unlike the minor or satiric prose about the Romanian townlets of 1900, Bogza’s piece of writing is regarded as a form of paradoxical rehabilitation of the provincial anonymity by a grid partly indebted to the vanguard. Without ceasing to represent a space of failure and unfulfillment, the province thus becomes a space of unusual experiences and of existential adventure, in agreement with the authenticist literature of the generation of the thirties.